Hubungan Self-Disclosure dengan Resiliensi pada Emerging Adult yang Mengalami Toxic Relationship dalam Berpacaran - Gracia Senkwen Vema Ruku; Wahyuni Kristinawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the relationship between self-disclosure and resilience among emerging adults who experience toxic relationships in dating contexts. Emerging adulthood is a developmental phase that is particularly vulnerable to involvement in toxic relationships, which may lead to emotional distress and hinder personal development. In dealing with such pressures, resilience becomes an essential capacity that enables individuals to recover and adapt positively. Self-disclosure, defined as the process of sharing personal information with others, is considered to play a role in helping individuals manage emotional experiences related to unhealthy relationships. This study employed a quantitative correlational method using an accidental sampling technique and involved 264 participants aged 18–29 years who had experienced or were currently experiencing toxic relationships, with the majority being female (84.1%). Data were collected using the Revised Self-Disclosure Scale (RSDS) and the Resilience Quotient Test (RQ Test). The results indicated a significant positive relationship between self-disclosure and resilience (r = 0.371; p < 0.05). These findings suggest that higher levels of self-disclosure are associated with higher levels of resilience in coping with the pressures resulting from toxic relationships. This study highlights the importance of self-disclosure as a factor related to the adaptive capacity of emerging adults and may serve as a consideration in the development of psychological interventions.